The improvement in grinding of inlet engine valves by the adoption of the most effective cuting fluid type - Da Silva, Eraldo Jannone [UNESP]; Bianchi, Eduardo Carlos [UNESP]; De Aguiar, Paulo Robero [UNESP]; Catai, Rodrigo Eduardo [UNESP] (SAE International, 2000)
In this paper is presented an experimental research in which the grinding of seating surfaces of inlet engine valves was improved by the adoption of the most effective cutting fluid type, matching the new requirements of cutting fluid application. Four different types of cutting fluids (straight oil and three different types of soluble oils) were analyzed. As qualitative and quantitative evaluation parameters of the performance of the cutting fluids, the roughness, the grinding wheel wear, the cutting force and the workpiece residual stress were determined. As a conclusion, the straight oil was the cutting fluid that presented the best results in all of the parameters analyzed. Copyright © 2000 Society of Automotive Engineers, Inc.
Keywords: Cutting fluid application; Cutting forces; Engine valves; Experimental research; Grinding wheel wear; Quantitative evaluation; Work pieces; Grinding (machining); Cutting fluids